Hypera folwacznyi spec. nov. aus dem Rhön-Gebirge (Coleoptera, Curculionidae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1975)
The middleeuropean Hypera folwacznyi spec. nov. is described and compared with the two similar species H. pandellei (Capiomont) from the Pyrenees and H. gestroi (Petri) from Sibiria. H. folwacznyi was discovered in the Rhön mountain. Nomenclatural Actsfolwacznyi Dieckmann, 1975 (Hypera), spec. n.